Molecular and Biochemical Characterization of Peripheral Blood MMP-2 Upregulation and TIMP-2 Downregulation in In-Stent Restenosis - Zhou, Xinghu; Ma, Hongbin; Qiao, Xuan; Bai, Bai (Journal of Medical Biochemistry, 2026)
Background: The matrix metalloproteinase-2/tissue inhibitor of metalloproteinase-2 (MMP-2/TIMP-2) axis is an important regulator of extracellular matrix turnover and vascular remodeling. Most previous studies have focused on either circulating protein levels or mRNA expression alone. Because PBMC mRNA expression and plasma protein concentration reflect different regulatory levels, paired cross-level analysis may provide a more complete characterization of peripheral blood MMP-2/TIMP-2 alterations in ISR. This study investigated the molecular and biochemical dysregulation of the peripheral blood MMP-2/TIMP-2 axis in patients with ISR.Methods: A total of 117 patients who underwent follow-up evaluation 6–12 months after coronary stent implantation were included, comprising 42 patients with ISR and 75 without ISR. Plasma MMP-2 and TIMP-2 concentrations were measured by ELISA, and MMP-2 and TIMP-2 mRNA expression levels in peripheral blood mononuclear cells were quantified by qPCR. Between-group differences, transcription–protein coupling, and associations with routine biochemical parameters were analyzed.Results: Patients with ISR showed increased MMP-2 expression and decreased TIMP-2 expression at both the mRNA and protein levels compared with patients without ISR. The altered MMP-2/TIMP-2 balance was consistent across transcriptional and protein measurements. TIMP-2 showed an inverse association with LDL-C at both levels, whereas the relationships between MMP-2-related measurements and hs-CRP, Hcy, and Lp(a) suggested heterogeneous biochemical regulation. Standardized qPCR- and ELISA-derived measurements showed consistent cross-level patterns, supporting the presence of parallel molecular and protein-level alterations of this axis.Conclusion: ISR is associated with a consistent peripheral blood MMP-2/TIMP-2 imbalance, involving increased MMP-2 expression and decreased TIMP-2 expression at both the mRNA and circulating protein levels. These findings provide pathobiochemical evidence that matrix-remodeling imbalance in ISR can be reflected in peripheral blood molecular and biochemical profiles.